Nitrogen fertilization offsets the N2O mitigating effects of cover‐crops and double‐crop soybean in a wheat–sorghum system. (4th March 2020) - Preza‐Fontes, Giovani; Tomlinson, Peter J.; Roozeboom, Kraig L.; Warren, Jason; Ruiz Diaz, Dorivar A.
Abstract: Cover crops (CCs) have been promoted as a key strategy to reduce nitrous oxide (N2 O) emissions by scavenging excess mineral nitrogen (N) after cash crop harvest. Optimum N fertilizer application rates are also critical to minimize N2 O emissions. Integrating these strategies requires research to understand how they interact to drive N2 O emissions. The objective was to evaluate N2 O emissions from winter wheat ( Triticum aestivum L.) harvest through the subsequent fallow period and grain sorghum [ Sorghum bicolor (L.) Moench] production phase of a long‐term, no‐till winter wheat–grain sorghum–soybean [ Glycine max (L.) Merr] cropping system. Fallow management treatments included chemical fallow (CF), double‐crop soybean (DSB), and two CCs: sorghum‐sudangrass ( Sorghum bicolor × sorghum bicolor var. sudanese) and daikon radish ( Raphanus sativus L.). Nitrogen fertilizer rates (0, 90, and 180 kg ha −1 ) were applied within 1 wk after sorghum planting. Soil nitrate‐N was consistently greater in CF than in the other treatments during the fallow period. Although, on average, CCs and DSB decreased cumulative N2 O emissions (cN2 O) by 1.75‐fold, during the fallow period compared to CF, they significantly increased cN2 O in the following sorghum crop. Emissions increased with greater applications of N regardless of how the fallow was managed, indicating that N fertilizer application in the following sorghum tended to offset any potential mitigating effects of CCs and DSB. These results highlight the importance of evaluating N2 O emissions for the system (fallow + following cash crop) to account for potential tradeoffs that could offset cN2 O mitigation when N fertilizer is applied.